Transparency for Robots and Autonomous Systems : Fundamentals, Technologies and Applications - Wortham, Robert H. (IET control, robotics and sensors series ;, 2020)
Based on scientific understanding and empirical evidence of how humans understand and interact with robotic and autonomous systems, this book reviews the concerns that have been raised around the deployment of AI and robots in human society, and the potential for disruption and harm.